Development of Auditory Intellectually Repetition (AIR) Based Student Worksheets for Science Subjects at SMPN 6 Sikur - Urwatil wutsqo amry; Baiq Anita Febriana; Lisawati (Institute of Educational, Research, and Community Service)
This study aims to develop Auditory Intellectually Repetition (AIR) based Student Worksheets (LKPD) for seventh grade science subjects at SMPN 6 Sikur which are valid based on graphical aspects, content feasibility, presentation feasibility, and linguistic aspects. This study uses the type of development (Research & Development) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). This research was carried out until the Implementation stage and followed by teacher and student response tests. The research object is a Student Worksheet based on Auditory Intellectually Repetition (AIR). The data collection instrument is a validation sheet filled out by 2 expert validators and one science teacher. The results of the data analysis obtained a validity score from the graphical aspect of 92.36%, content feasibility of 91.68%, presentation feasibility of 89.58%, language of 93.75%, and a total average value of 91.84% with the criteria of